Biochemical and Biological Functions of the N-Terminal, Noncatalytic Domain of Extracellular Signal-Regulated Kinase 2 - Eblen, Scott T. (American Society for Microbiology, 2001)
Extracellular signal-regulated kinase 1 (ERK1) and ERK2 are important components in signal transduction pathways involved in many cellular processes, including cell differentiation and proliferation. These proteins consist of a central kinase domain flanked by short N- and C-terminal noncatalytic domains. While the regulation of ERK2 by sequences within the kinase domain has been extensively studied, little is known about the small regions outside of the kinase domain. We performed mutational analysis on the N-terminal, noncatalytic domain of ERK2 in an attempt to determine its role in ERK2 function and regulation. Deleting or mutating amino acids 19 to 25 (ERK2-Δ19-25) created an ERK2 molecule that could be phosphorylated in response to growth factor and serum stimulation in a MEK (mitogen-activated protein kinase kinase or ERK kinase)-dependent manner but had little kinase activity and was unable to bind to MEK in vivo. Since MEK acts as a cytoplasmic anchor for the ERKs, the lack of a MEK interaction resulted in the aberrant nuclear localization of ERK2-Δ19-25 mutants in serum-starved cells. Assaying these mutants for their ability to affect ERK signaling revealed that ERK2-Δ19-25 mutants acted in a dominant-negative manner to inhibit transcriptional signaling through endogenous ERKs to an Elk1-responsive promoter in transfected COS-1 cells. However, ERK2-Δ19-25 had no effect on the phosphorylation of RSK2, an ERK2 cytoplasmic substrate, whereas a nonactivatable ERK (T183A) that retained these sequences could inhibit RSK2 phosphorylation. These results suggest that the N-terminal domain of ERK2 profoundly affects ERK2 localization, MEK binding, kinase activity, and signaling and identify a novel dominant-negative mutant of ERK2 that can dissociate at least some transcriptional responses from cytoplasmic responses.